Nanoparticles production of bioactive compounds from cardamom fruit ethanol extract - Sherlin Marthalina putri Natty; Donn Richard Ricky (Science Midwifery, 2023)
Research in recent years has focused on developing nanoparticle bioactive compounds extracted from ethanol cardamom due to its potential health benefits. Cardamom (Elettaria cardamomum) is a spice plant commonly used in traditional medicine to treat various health problems, such as digestive disorders, headaches, and respiratory issues. This study explored the method of producing nanoparticles from bioactive compounds of cardamom ethanol extract using gas chromatography-mass spectroscopy (GC-MS) and nanoparticle techniques. The steps for producing nanoparticles through this method consist of several stages, starting with identifying bioactive compounds using GC-MS, followed by producing nanoparticles using Nanoparticle techniques. The measurement results of the prepared chromatography concentrates were performed using Shimadzu GC-MS QP2010 Ultra equipment, and the total ion chromatogram (TIC) of the measured compound molecules was obtained. This study found that the size or percentage of each peak area in the concentrate correlates with the high order of the peak, thus indicating the compound content in the concentrate.